The Cleansing of New York,' Puck Magazine, 1900 (Keppler & Schwarzmann, 1900)
Issue of 'Puck' (volume XLVII (volume 47), no. 1204) humor magazine featuring caricatures of William Randolph Hearst and his yellow journalism and another man being held up by the hand of the law. The title and text beneath read "The Cleansing of New York. Why not make a clean job of it while we're at it?" The reverse side features a couple of illustrations ("The Eternal Feminine" and "Puckographs. - XLVI") and numerous humorous anecdotes and one-liners. Circa April 4th, 1900.